Cost-effectiveness analysis of combining traditional Chinese medicine in the treatment of hypertension: compound Apocynum tablets combined with Nifedipine sustained-release tablets vs Nifedipine sustained-release tablets alone - Qian Xu; Nan Yang; Shuang Feng; Jianfei Guo; Qi-bing Liu; Ming Hu (BMC, 2020)
Abstract Background We evaluated the long-term cost-effectiveness of antihypertensive traditional Chinese medicines (TCMs) and to compare the cost-effectiveness of a combined treatment consisting of compound Apocynum tablets and Nifedipine sustained-release tablets with the cost-effectiveness of treatment with Nifedipine sustained-release tablets alone. Methods A Markov model was used to simulate the potential incremental cost-effectiveness per quality-adjusted life year (QALY) to be gained from compound Apocynum tablets and Nifedipine sustained-release tablets compared with Nifedipine sustained-release tablets alone. Model parameter estimates were informed by previously published studies. The direct medical costs of outpatients with hypertension were estimated from the health care provider's perspective. A 5% annual discount rate was applied to both costs and QALYs. Results TCMs combined with Nifedipine sustained-release tablets group generated a total 20-year cost of 11,517.94 RMB (US $1739.87), whereas Nifedipine sustained-release tablets alone group resulted in a 20-year cost of 7253.71 RMB (US $1095.73). TCMs combined with Nifedipine sustained-release tablets group resulted in a generation of 12.69 QALYs, whereas Nifedipine sustained-release tablets alone group resulted in 12.50. The incremental cost-utility ratio was 22,443.32 RMB (US $3390.23) per QALY. Considering the threshold of 1 GDP per capita in China in 2018 (US $9764.95), the combination of compound Apocynum tablets and Nifedipine sustained-release tablets was a cost-effective strategy. One-way and probabilistic sensitivity analysis showed unchanged results over an acceptable range. Conclusions Combining Traditional Chinese Medicines with chemical medicines is more cost-effective strategy in the treatment of hypertension.